2021
DOI: 10.3389/fphar.2021.690432
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Traditional Knowledge to Develop Effective Medicines for the Treatment of Leishmaniasis

Abstract: Leishmaniasis is a neglected tropical disease that affects people living in tropical and subtropical areas of the world. There are few therapeutic options for treating this infectious disease, and available drugs induce severe side effects in patients. Different communities have limited access to hospital facilities, as well as classical treatment of leishmaniasis; therefore, they use local natural products as alternative medicines to treat this infectious disease. The present work performed a bibliographic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 116 publications
0
18
0
Order By: Relevance
“…Plants are important sources of active principles against Leishmania as shown by a study in Pakistan that reported that 23 plants were tested, using mostly leaves of the genus Lamiaceae and, out of these plants, only 11 were tested in vitro with good results regarding inhibition of the parasite [16]. Another study which also mostly used leaves indicated that among the plants most used by folk medicine to treat leishmaniasis were Carica papaya (Caricaceae), Cedrela odorata (Meliaceae), Musa paradisiaca (Musaceae), and Nicotiana tabacum (Solanaceae) [17]. A study in Mexico showed that dichloromethane and dichloromethane/methanol extracts of Schinus molle, dichloromethane of Lantana camara, and aqueous extracts of Prosopis laevigata had an inhibitory effect on Leishmania amazonensis, although this study also tested aqueous, dichloromethane and dichloromethane/methanol extracts of the leaves and branches of P. guajava against L. amazonensis; and no active or speci c effect was observed [18].…”
Section: Resultsmentioning
confidence: 99%
“…Plants are important sources of active principles against Leishmania as shown by a study in Pakistan that reported that 23 plants were tested, using mostly leaves of the genus Lamiaceae and, out of these plants, only 11 were tested in vitro with good results regarding inhibition of the parasite [16]. Another study which also mostly used leaves indicated that among the plants most used by folk medicine to treat leishmaniasis were Carica papaya (Caricaceae), Cedrela odorata (Meliaceae), Musa paradisiaca (Musaceae), and Nicotiana tabacum (Solanaceae) [17]. A study in Mexico showed that dichloromethane and dichloromethane/methanol extracts of Schinus molle, dichloromethane of Lantana camara, and aqueous extracts of Prosopis laevigata had an inhibitory effect on Leishmania amazonensis, although this study also tested aqueous, dichloromethane and dichloromethane/methanol extracts of the leaves and branches of P. guajava against L. amazonensis; and no active or speci c effect was observed [18].…”
Section: Resultsmentioning
confidence: 99%
“…(2S,3R,4R)-3-Hydroxy-4-methyl-2-(n-eicosanil)butanolide (3). Amorphous white solid, 100% purity by HPLC.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…The treatment of leishmaniasis is limited and involves using toxic drugs such as antimonial derivatives, amphotericin B, and miltefosine. Based on this scenario, the search for new hit compounds is crucial, and natural products can provide inspiring molecules for drug discovery studies against this neglected tropical diseases [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 25 drugs or combinations have been used for humans in leishmaniasis [22][23][24]. This high number suggests that there are limitations in the currently available chemotherapy.…”
Section: Chemotherapy Of Leishmaniasis: Current Drugs Limitations And...mentioning
confidence: 99%